2022
DOI: 10.1155/2022/9969729
|View full text |Cite
|
Sign up to set email alerts
|

Calycosin Ameliorates Bleomycin-Induced Pulmonary Fibrosis via Suppressing Oxidative Stress, Apoptosis, and Enhancing Autophagy

Abstract: Calycosin (CA) is a flavonoid extracted from the root of Astragalus membranaceus and has antioxidant, anti-inflammation, and antiapoptosis properties. The objective of this study was to investigate the efficacy of CA in protecting against pulmonary fibrosis. CA (14 mg/kg) and SB216763 (20 mg/kg) were administrated to bleomycin-induced pulmonary fibrosis mice for 3 weeks. The results concluded that CA alleviated the inflammation and collagen deposition in pulmonary fibrosis. In addition, CA reduced MDA level, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The results of this study revealed clearly significant oxidative disturbance after the BLM treatment as indicated in MDA, SOD, and CAT levels evaluation which corroborates with those of Liu et al 28 Interestedly, OLE induced significant restoration of these activities. Indeed, treatment with OLE induced a significant increase in CAT activity in lung parenchyma which was dropped after the BLM treatment, and these results corroborate with those of Rouibah et al 29 and Elgebaly et al 30 OLE has been described to protect rats against oxidative stress by inducing a reduction/inhibition of the ROS formation which can improve CAT production.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study revealed clearly significant oxidative disturbance after the BLM treatment as indicated in MDA, SOD, and CAT levels evaluation which corroborates with those of Liu et al 28 Interestedly, OLE induced significant restoration of these activities. Indeed, treatment with OLE induced a significant increase in CAT activity in lung parenchyma which was dropped after the BLM treatment, and these results corroborate with those of Rouibah et al 29 and Elgebaly et al 30 OLE has been described to protect rats against oxidative stress by inducing a reduction/inhibition of the ROS formation which can improve CAT production.…”
Section: Discussionsupporting
confidence: 91%
“…One previous study showed that TJ‐98 ameliorates organ fibrosis [20]. This study suggests that the inhibition of IL‐1β may be involved in the amelioration of intestinal shortening and fibrosis by TJ‐98.…”
Section: Discussionmentioning
confidence: 57%
“…Calcineurin inhibitors, including tacrolimus, have short-term, but not long-term, therapeutic effects [20,21]. There have been no reports on the effects of TJ-98 with a calcineurin inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that calycosin effectively ameliorated the severity of fibrosis in BLM-induced mouse models by repressing EMT and blocking the AKT/GSK3β/β-catenin pathway [ 92 ]. Additionally, calycosin has demonstrated a highly potent inhibitory effect against inflammation and collagen deposition in BLM-induced mice while simultaneously enhancing the Nrf2/HO-1 pathway and inducing apoptosis [ 93 ]. Notably, calycosin promoted the upregulation of LC3, beclin1, and PINK1 and reduced p62 expression while amplifying the expression of LAMP1 and TFEB; thus, resulting in enhanced autophagy and the inhibition of lysosome enzyme release from ruptured lysosomes [ 93 ].…”
Section: Current Status Of the Natural Flavonoid For Anti-pulmonary F...mentioning
confidence: 99%
“…Additionally, calycosin has demonstrated a highly potent inhibitory effect against inflammation and collagen deposition in BLM-induced mice while simultaneously enhancing the Nrf2/HO-1 pathway and inducing apoptosis [ 93 ]. Notably, calycosin promoted the upregulation of LC3, beclin1, and PINK1 and reduced p62 expression while amplifying the expression of LAMP1 and TFEB; thus, resulting in enhanced autophagy and the inhibition of lysosome enzyme release from ruptured lysosomes [ 93 ]. Furthermore, calycosin inhibited TGF-β1-induced EMT and alleviated pulmonary fibrosis by regulating the miR-375/YAP1 signaling pathway [ 94 ].…”
Section: Current Status Of the Natural Flavonoid For Anti-pulmonary F...mentioning
confidence: 99%